Non-invasive Autonomic Neuromodulation Is Opening New Landscapes for Cardiovascular Diseases - Chen, Mingxian; Wang, Songyun; Li, Xuping; Yu, Lilei; Yang, Hui; Liu, Qiming; Tang, Jianjun; Zhou, Shenghua (Frontiers in Physiology, 2020)
Autonomic imbalance plays a crucial role in the genesis and maintenance of cardiac disorders. Approaches to maintain sympatho-vagal balance in heart diseases have gained great interest in recent years. Emerging therapies However, certain types of emerging therapies including direct electrical stimulation and nerve denervation require invasive implantation of a generator and a bipolar electrode subcutaneously or result in autonomic nervous system (ANS) damage, inevitably increasing the risk of complications. More recently, non-invasive neuromodulation approaches have received great interest in ANS modulation. Non-invasive approaches have opened new fields in the treatment of cardiovascular diseases. Herein, we will review the protective roles of non-invasive neuromodulation techniques in heart diseases, including transcutaneous auricular vagus nerve stimulation, electromagnetic field stimulation, ultrasound stimulation, autonomic modulation in optogenetics, and light-emitting diode and transcutaneous cervical vagus nerve stimulation (gammaCore).